Elegiarum Libri Quattuor Edizione critica commentata - Kochanowski, Jan (Biblioteca di Studi Slavistici, 2019)
This volume contains the critical edition of the Latin elegies written by the most important poet of the Polish Renaissance, as well as a philological commentary . The comment, in particular, does not only refer to the collection of similia, but also analyses Jan Kochanowski's ways of "imitatio" (imitation), underlining his extraordinary poetic skills as well as his vibrant and lively relationship with classical texts, which he reuses cleverly to satisfy his own needs for meaning.